Peculiarities of implementing the personality-oriented teaching technique in the process of acquiring legal disciplines at higher educational institutions (other than law schools) - Vasilyeva, N. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the peculiarities of teaching legal disciplines at higher educational institutions at the present stage, when the main objective of the reforms taking place in Ukraine is the development of citizens’ awareness of the absolute importance of law and its universal character. Today, the legal consciousness of the citizens of the state should be formed not only by means of the system of an effective mechanism of legal regulation and application of legal norms, but first of all through legal education. The purpose of vocational training of the future teacherengineer at institutions of higher learning is the formation of his/her professional-legal competence, that is a set of professional legal knowledge and skills, and readiness for all types of legal actions in engineering and pedagogical activities. The value of personality-oriented learning technology lies in its innovative orientation, with the establishment of relations of equal interaction between the participants of the educational process, which allows ensuring the success of the process of legal competences formation and comprehensive development of the future engineer-teacher’s personality.